Assessment of MR stereotactic imaging and image co-registration accuracy for 3 different MR scanners by 3 different methods/phantoms: phantom and patient study - Paštyková, Veronika; Novotný, Josef; Veselský, Tomáš; Urgošík, Dušan; Liščák, Roman; Vymazal, Josef (Journal of neurosurgery, 2018)
OBJECTIVEThe aim of this study was to compare 3 different methods to assess the geometrical distortion of two 1.5-T and one 3-T magnetic resonance (MR) scanners and to evaluate co-registration accuracy. The overall uncertainty of each particular method was also evaluated.METHODSThree different MR phantoms were used: 2 commercial CIRS skull phantoms and PTGR known target phantom and 1 custom cylindrical Perspex phantom made in-house. All phantoms were fixed in the Leksell stereotactic frame and examined by a Siemens Somatom CT unit, two 1.5-T Siemens (Avanto and Symphony) MRI systems, and one 3-T Siemens (Skyra) MRI system. The images were evaluated using Leksell GammaPlan software, and geometrical deviation of the selected points from the reference values were determined. The deviations were further investigated for both definitions including fiducial-based and co-registration-based in the case of the CIRS phantom images. The same co-registration accuracy assessment was also performed for a clinical case. Patient stereotactic imaging was done on 3-T Skyra, 1.5-T Avanto, and CT scanners.RESULTSThe accuracy of the CT scanner was determined as 0.10, 0.30, and 0.30 mm for X, Y, and Z coordinates, respectively. The total estimated uncertainty in distortion measurement in one coordinate was determined to be 0.32 mm and 0.14 mm, respectively, for methods using and not using CT as reference imaging. Slightly more significant distortions were observed when using the 3-T than either 1.5-T MR units. However, all scanners were comparable within the estimated measurement error. Observed deviation/distortion for individual X, Y, and Z stereotactic coordinates was typically within 0.50 mm for all 3 scanners and all 3 measurement methods employed. The total radial deviation/distortion was typically within 1.00 mm. Maximum total radial distortion was observed when the CIRS phantom was used; 1.08 ± 0.49 mm, 1.15 ± 0.48 mm, and 1.35 ± 0.49 mm for Symphony, Avanto, and Skyra, respectively. The co-registration process improved image stereotactic definition in a clinical case in which fiducial-based stereotactic definition was not accurate; this was demonstrated for 3-T stereotactic imaging in this study. The best results were shown for 3-T MR image co-registration with CT images improving image stereotactic definition by about 0.50 mm. The results obtained with patient data provided a similar trend of improvement in stereotactic definition by co-registration.CONCLUSIONSAll 3 methods/phantoms used were evaluated as satisfactory for the image distortion measurement. The method using the PTGR phantom had the lowest uncertainty as no reference CT imaging was needed. Image co-registration can improve stereotactic image definition when fiducial-based definition is not accurate.
Keywords: Tomography, X-Ray Computed; MRI = magnetic resonance imaging; software; Skull; Phantoms, Imaging; CT = computed tomography; PET = positron emission tomography; počítačová rentgenová tomografie; lidé; Models, Anatomic; phantom measurement; stereotactic methods; počítačové zpracování obrazu; Artifacts; anatomické modely; Stereotaxic Techniques; magnetická rezonanční tomografie; stereotaktické techniky; stereotactic MR imaging; fantomy radiodiagnostické; Software; lebka; Reproducibility of Results; artefakty; reprodukovatelnost výsledků; stereotactic radiosurgery; Image Processing, Computer-Assisted; Humans; Magnetic Resonance Imaging; image co-registration